Reconciling accessibility benefits with user benefits - Jonas Eliasson (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2020)
This paper asks whether transport policy assessments should use accessibility benefits as a key measure instead of user benefits. It argues that both measures are equivalent if accessibility measures are based on transport users' own preferences and if the same principle is used to aggregate benefits. The paper also addresses how distributional questions can be addressed within this approach.
Keywords: 330